TEACHING ENGLISH PRONUNCIATION THROUGH SONGS - Abdusalimova Ruxshona,; Zulfiya Axmedova, (TADQIQOTLAR, 2026)
Annotation: In recent years, the importance of effective pronunciation in learning English as a foreign language has gained significant attention. Pronunciation plays a crucial role in communication, as it directly affects learners’ ability to be understood and to understand others. Despite its importance, many learners face difficulties in mastering English pronunciation due to differences between their native language and English sound systems. Traditional methods of teaching pronunciation often focus on repetition,  drills,  and  isolated  sound  practice,  which  can  be  monotonous  and  less engaging for students. As a result, there is a growing need for more interactive and motivating approaches in language classrooms. One such innovative method is the use of songs as a teaching tool. Songs provide authentic language input, natural rhythm, stress,  and  intonation  patterns,  making  them  an  effective  resource  for  improving pronunciation.  Through  listening  and  singing  along,  learners  can  develop  better phonetic  awareness,  improve  their  listening  skills,  and  internalize  correct pronunciation  in  an  enjoyable  way.  Moreover,  songs  create  a  relaxed  and  positive learning environment, which reduces anxiety and increases students’ motivation. This article aims to explore the effectiveness of teaching English pronunciation through  songs,  highlighting  its  benefits,  practical  techniques,  and  its  impact  on learners’ pronunciation skills.